The Influence of Monitoring, Evaluation, And Teamwork Effectiveness on Principle 7 Correct Implementation of Drug Administration in Non-Covid-19 Inpatient in Hospitals - Rini Anggraini; Santy Deasy Siregar; Rafael Ginting (CV. Inara, 2023)
Errors in drug administration were ranked first (24.8%) of the top 10 incidents reported in hospitals. The types of errors that caused death in patients included 40.9%, wrong dose, 16% wrong drug, and 9.5% wrong route of administration. The purpose of this study was to analyze the influence of monitoring, evaluation, and teamwork effectiveness on the implementation of the 7 correct principles of drug administration. This research is a quantitative analysis with a cross-sectional approach. The research was conducted at Hospital Pematang Siantar. The study population was 103 people and all of them were used as samples (total sampling). Data were analyzed using univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level (a=0.05). The results showed that the implementation of the 7 correct principles of drug administration at the non-Covid-19 Inpatient Installation at Hospital in Pematang Siantar was influenced by monitoring variables (p=0.000), evaluation (p=0.036), teamwork effectiveness (p=0.042). The monitoring variable has a greater influence on the implementation of the 7 right principles of drug administration with a value of OR = 10.643 meaning that nurses who say monitoring is good have the opportunity to implement the 7 right principles of drug administration properly by 10.6 times higher than nurses who say monitoring is not good. The conclusion of the study is that monitoring, evaluation and teamwork effectiveness affect the implementation of the 7 principles of correct drug administration. It is recommended that the hospital can carry out continuous monitoring and evaluation regarding the procedures that have been established as a benchmark for achieving SOPs that are applied in implementing the 7 correct principles of drug administration. Nurses need to increase the effectiveness of teamwork (teamwork) so as to minimize the adverse impact on the patients served.